1988
DOI: 10.1111/j.1365-3091.1988.tb00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft‐sediment deformation (fluid escape) features in a coarse‐grained pyroclastic‐surge deposit, north‐central New Mexico

Abstract: The Puye Formation in north‐central New Mexico is a very coarse‐grained fanglomerate which was deposited on the eastern flank of the Jemez caldera. Pyroclastic deposits occur within the Puye in the form of airfall pumice beds and the remnant of at least one pyroclastic‐surge deposit. This pyroclastic‐surge deposit shows the effects of fluidization and soft‐sediment deformation in the form of: (1) intrusive sedimentary plumes; (2) upwardly injected gravelly pipes; (3) ‘pocket structures’ similar to those of Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Phoenix (1958) concluded that sandstone cylinders in the Carmel Formation in north‐central Arizona were created by infilling of cylindrical cavities that formed as spring pits where hydrostatic pressure had been locally relieved. Palaeosprings have been used in several theories to account for the hydrostatic pressure required to fluidize sand (Gabelman, 1955; Allen, 1961; Schlee, 1963; Megrue & Kerr, 1965; Davidson, 1967; Moench & Schlee, 1967; Lowe, 1975; Neumann‐Mahlkau, 1976; Hannum, 1980; Nocita, 1988; Decker, 1990; Collinson, 1994).…”
Section: Previous Workmentioning
confidence: 99%
“…Phoenix (1958) concluded that sandstone cylinders in the Carmel Formation in north‐central Arizona were created by infilling of cylindrical cavities that formed as spring pits where hydrostatic pressure had been locally relieved. Palaeosprings have been used in several theories to account for the hydrostatic pressure required to fluidize sand (Gabelman, 1955; Allen, 1961; Schlee, 1963; Megrue & Kerr, 1965; Davidson, 1967; Moench & Schlee, 1967; Lowe, 1975; Neumann‐Mahlkau, 1976; Hannum, 1980; Nocita, 1988; Decker, 1990; Collinson, 1994).…”
Section: Previous Workmentioning
confidence: 99%
“…If the disturbed beds had been slightly more destabilized and permitted entrainment, the same configuration would be observed. Such impact SSDs would explain the oversteepened truncations and be at the origin of some of the "chute and pool" structures (see also Nocita, 1988). This would also explain the observation by Schmincke et al (1973) that "chute and pool" structures occur in rather proximal parts, since ballistic blocks are likely to land closer to the crater than the total distance traveled by a PDC.…”
Section: A Trigger For "Chute and Pool" Structures?mentioning
confidence: 86%
“…4h) may have been oversteepened by the rearrangement of the underlying sediment. Such a process was readily suggested by Nocita (1988), although the sediments of their study were later reinterpreted as fluvial rather than from PDCs (McPherson et al, 1989), without changing the accuracy of the process. The coarse lag breccia on top of the central depression may either indicate that the impacting block stayed in place and acted upon the depositional dynamics, resuspended fines during impact, or be a simple infill of the topography.…”
Section: Impact Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith & Katzman () noted the ease of incorrectly identifying aeolian tuffs as surge deposits in proximal settings. Nocita () inadvertently described soft‐sediment deformation in the Puye fan, New Mexico, as affecting pyroclastic surge deposits, but later retracted his interpretation in reply to a comment by McPherson et al . () that demonstrated a fluvial origin for those deposits.…”
Section: Introductionmentioning
confidence: 99%